Factors Affecting The Decision To Use Apple Pay Wireless E-Wallet - Thi Thanh, Hoang; Truong, To Cong; Dong Tan , Thai; Quoc Manh, Ha (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study investigates the factors influencing the decision to use Apple Pay in Vietnam. It seeks to understand how various perceptions and expectations shape consumer behavior toward adopting wireless payment systems. Theoretical framework: The research framework is built upon established theories related to technology acceptance and consumer behavior. Key influencing factors examined include Security Perception, Utility Perception, Performance Expectation, Usage Attitude, Ecosystem, and Ease of Use. Design/methodology/approach: A mixed-methods approach was utilized, combining qualitative and quantitative research methods. A survey was conducted with a sample of 350 consumers in Vietnam. The collected data was analyzed using SmartPLS 3.9 software to ensure the reliability and validity of the measurements. Findings: The analysis reveals that Security Perception significantly impacts the decision to use Apple Pay. Other factors, such as utility perception, performance expectation, and ease of use, also contribute to adopting this wireless electronic wallet. Research, Practical & Social Implications: The findings provide valuable insights for stakeholders in the digital payment ecosystem, particularly in enhancing the user experience and addressing security concerns. For practitioners, the study suggests strategies to improve consumer acceptance and usage of Apple Pay. Socially, the research underscores the shift in consumer attitudes toward mobile payment solutions in a technologically advancing environment. Originality/value: This study adds to the literature on mobile payment systems by focusing on the specific context of Vietnam, where adopting such technologies is on the rise. It provides a nuanced understanding of the factors driving consumer decisions to use wireless payment services, with implications for academic research and practical applications in the digital payments market.